Prawo ucznia do bycia wysłuchanym w sytuacji konfliktu. Wybrane aspekty i ujęcia - Janeczko-Janicka, Marta (Pedagogika Społeczna Nova, 2024)
Children have the right to express their views freely in all matters affecting them, with due weight being given to the child’s views in accordance with the child’s age and maturity. Studies show that these rights are not always respected in schools and that violations often occur at the stage of drafting internal rules – statutes. At school, pupils are inevitably confronted with difficult situations, such as conflicts with peers or teachers. These situations can have a negative impact on individual and social functioning. Research shows that the rate of peer violence in Poland remains high and that children experience it most frequently in the school environment. At school, children’s rights are also violated by teachers (psychological and physical violence, white-gloved violence). This article is an attempt to capture the “voice of the pupil” in a conflict situation at school and to answer the question of how this voice (dis)resonates depending on the degree of rights violation, the dominant model of educational relations at school, the implemented ways and methods of resolving difficult and conflict situations.